Thirty Two Years Male Patient with Adult Stillâs Disease (Journal of Medicine, 2008)
A rare systemic inflammatory disorder is Adult onset Still's disease (AOSD), characterized by diverse clinical and laboratory findings, which is often difficult to diagnose. It is responsible for a significant proportion of cases of acute febrile illness in young adults. Adult Onset Stills Disease (AOSD) usually affects multiple organs, but it is a diagnosis of exclusion. Here we describe a case of a 32-year old patient with fever of unknown etiology, arthralgia, sore throat and skin rash. The final diagnosis of Still's disease was made by clinical and laboratory criteria and exclusion of other causes of similar presentation. Â  DOI = 10.3329/jom.v9i1.1428 J MEDICINE 2008; 9 : 58-61